(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
In this article, the formation of realism took place in European countries almost at the same time - in the 20s-40s of the XIX century. It became a leading trend in world literature. At the same time, this means that the literary process of this period cannot be reduced only to the realist system. The term "classical" (ie, "exemplary") is sometimes used alongside the definition "critical" to describe nineteenth-century realism. Realism of the 19th century is one of the highest achievements of such realistic art, and the works of writers such as Balzac, Stendhal, Dickens, and Merimee are unique examples of artistic creativity and models for writers of later periods